Desirable Dense Neighbourhoods: An Environmental Psychological Approach for Understanding Community Resistance to Densification - Nematollahi, S.; Tiwari, Reena; Hedgecock, D. (2015)
This article examines an environmental psychological approach to exploring the attitudes of urban residents towards what they consider to be a ‘desirable dense’ neighbourhood. Socio-cultural expectations of high-density developments are explored through an analysis of residents’ perceptions of what constitutes a desirable high-density environment. The article presents specific findings identifying influences on residents’ attitudes to urban densification derived from three case studies of designated transit-oriented development (TOD) areas located in the Perth Metropolitan Region. It was found that community resistance towards future higher-density developments is rooted in the current socio-cultural context of the area. Community resistance may be driven by the physical quality of developments (such as building heights, overshadowing), however, deeper concerns are allied to the uncertain social outcomes that are the product of new development. A dominant cultural characteristic such as a disinclination to socialise with diverse people is found to be a negative response to dense neighbourhoods in all the case studies. This characteristic is more evident in populations of high socio-economic status. These areas are usually close to the central business district (CBD) where many infill high-density developments have been proposed.